Mapping agricultural GVC in the European Union - Dominik Kohut (World Economy and Policy (WEP), 2023)
Agriculture represents just a small part of the production and international trade. Although its share is little compared to the manufacturing and services sector, agriculture is still the source of an essential product for humankind - food. One of the trends that changed international trade significantly in recent history was globalization. Global value chains (GVC) affect ways of working, not just in manufacturing sectors. This paper focuses on mapping agricultural GVC in the European Union. General GVC indicators such as backward and forward participation are put in the context of employment, primary production, and productivity in agriculture for all EU27 member states. International input-output tables were the main source for GVC analysis. Eurostat and FAO (Food and Agriculture Organization) databases were used for additional sector information and statistics regarding agricultural production. Analysis of the agricultural sector shows significant differences between various member states in terms of employment, productivity, and GVC participation. To fully understand these differences, it is also necessary to bring into the context data on primary production in the sector and farm holdings information. The paper also covers the value flows from industries producing intermediates for agriculture, the value added of the sector, and the destination where agricultural products are consumed or used as intermediates in the production process. Results of value flow analysis show that most of the value produced in the agricultural sector is used in the food manufacturing sector or directly consumed by households' final demand.
Keywords: F10; F60; Q17; 330; Value added; European Union; Trade in value-added; Value chains; Agriculture; Value flows